ANALISIS PENGARUH PERDAGANGAN INTERNASIONAL DAN KURS TERHADAP CADANGAN DEVISA DI INDONESIA PERIODE 2019-2022 - Pipit Puspitasari; Rahmi Aulia Putri; Febri Azka Dzikrullah (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research is aimed to analyze the effect of exports, imports and exchange rates on Indonesia's foreign exchange reserves for the period 2019 – 2022. The variables which are used in this research are foreign exchange reserves, exports, imports and exchange rates. The data in this research were gathered from secondary data in the BPS and Bank Indonesia. VECM was applied as the methode for this research. The results which are showed are that in the short term, the export and import variables had a negative and insignificant effect on the foreign exchange reserve variable, but the exchange rate variable had a not significant positive effect on the foreign exchange reserve variable. In the long run, the variables of exports, imports and exchange rates have a significant and positive effect on foreign exchange reserves.